Peran Critical Thinking Sebagai Tameng Digital Bagi Generasi Z - Adinda Puspita Sari; M. Chaerul Rizky, Devi Surya Aritonang, Aathifah Sabiya, David Steven Rajagukguk (Pascasarjana STIE Amkop Makassar, 2026)
This study examines the role of critical thinking as a digital shield for Generation Z in navigating an increasingly complex, dynamic, and information-saturated digital environment in which accuracy and credibility are not always guaranteed. As a generation that has grown and developed alongside rapid technological advancement, Generation Z experiences a high level of exposure to social media, digital platforms, and algorithm-driven systems that indirectly shape their mindset, attitudes, and decision-making processes. This condition presents various challenges, including the widespread circulation of misinformation and disinformation, cybersecurity risks, digital manipulation, opinion polarization, and exposure to harmful content that may negatively influence individual behavior. In this context, critical thinking emerges as a strategic cognitive skill that enables individuals to objectively analyze information, evaluate the credibility of digital sources, understand algorithmic bias, and make rational and responsible decisions. This study employs a descriptive qualitative approach to explore how critical thinking functions as a protective mechanism in strengthening Generation Z’s digital awareness and promoting ethical and prudent digital behavior. The findings indicate that individuals with strong critical thinking skills tend to be more selective in consuming and sharing information, are better able to identify misleading or harmful content, and demonstrate greater resilience against negative influences in the digital environment. Furthermore, the integration of critical thinking skills into digital literacy programs has been shown to enhance Generation Z’s ability to filter information, manage digital risks, and adapt to rapid technological changes. Therefore, critical thinking not only serves as an intellectual competence but also acts as an essential digital shield that supports safe, adaptive, and sustainable digital interactions in the era of digital transformation.Keywords : critical thinking; digital shield; generation z